Ab initio nuclear shape coexistence and emergence of island of inversion around N = 20 - E.F. Zhou; C.R. Ding; J.M. Yao; B. Bally; H. Hergert; C.F. Jiao; T.R. Rodríguez (Physics Letters B)
We extend a nuclear ab initio framework based on chiral two- and three-nucleon interactions to investigate shape coexistence and the degradation of the N=20 magic number in both even-even and odd-even magnesium isotopes. The quantum-number projected generator coordinate method, combined with the in-medium similarity renormalization group (IMSRG), is employed to compute their low-lying states. This approach reasonably reproduces the coexistence of weakly and strongly deformed states at comparable energies, and allows us to track the emergence of the N=20 island of inversion through the continuous IMSRG evolution of the chiral Hamiltonian. Our results indicate that the ground state of 33Mg with spin-parity 3/2− is predominantly a strongly deformed configuration with Kπ=3/2−, while the lowest 7/2− state is predicted to be a shape isomer, consisting of a mixture of weakly deformed configurations with different K values. The results highlight the essential roles of both dynamical and static collective correlations in reproducing the ordering of nuclear states with distinct shapes.